The Challenge of Nuclear Terror - Mishra, Sitakanta (New Delhi K.W. Publishers, 2008)
Study based on open source information and personal interaction with eminent Indian nuclear scientists.
Include Picture and Appendix
Keywords: Nuclear terrorism -- Nuclear terrorism--Prevention -- India